Modelling Key Obstacles Hindering The Business Performance of Small and Medium Enterprises Within The Mangaung Metropolitan Area in South Africa - Kareli, Bennedict Motsamai; Maziriri, Eugine Tafadzwa; Chuchu, Tinashe (School of Business, IPB University (SB-IPB), 2023)
SMEs play a crucial role in South Africa's economic growth, contributing to production capacity and job creation. This study focused on understanding the obstacles hindering SMEs and specifically examined the impact of financial, management, corruption, and infrastructure obstacles on SME performance in the Mangaung metropolitan area. Data was collected through an online survey from 240 SME owners/managers using a non-probability convenience sampling method. The results, analyzed using SPSS and SmartPLS, revealed that financial, management, corruption, and infrastructure obstacles have a negative effect on SME performance in the Mangaung metropolitan area. The findings have theoretical implications for entrepreneurship research and provide insights for SME managers to improve their entrepreneurial endeavors. The study also has policy implications, suggesting the need for revised credit access policies with lower interest rates for SMEs. Overall, this research contributes new knowledge to the entrepreneurship and small business management literature in the African context, which has been under-researched in academia. Keywords: job creation, corruption, infrastructure obstacles, business performance, SMEs